Disease-based traumas transform lives: A qualitative study focused on healthcare professionals1This study was produced from the doctoral thesis titled "A Study on the Transformative Role of Health Workers' Disease Traumas in Their Lives" prepared by Dilruba İzgüden and conducted under the supervision of Ramazan Erdem. (July 2022) - İzgüden, Dilruba and Erdem, Ramazan
Abstract: Rationale: Traumas occur at unexpected moments and become a turning point in life and can cause people to experience transformations. While these transformations can progress negatively, it is also possible for people to experience positive transformations after trauma (post-traumatic growth). Objective: This study aims to reveal how the physicians and nurses with disease-based traumas make sense of their experiences to provide better insights into the transformative power of these traumas. Both social life and work-life were evaluated from the social dimensions of trauma. Also, the advantages and disadvantages of being a health professional in this process were examined. Methods: Qualitative research method was used in the study and data were obtained through interviews with 23 participants who experienced the case of disease-based trauma. As a result of the interviews, 253 pages of data were obtained. The data were subjected to thematic analysis and the Maxqda Program was used. Results: The data obtained through the interviews conducted within this attempt were categorized into parent themes such as being a health worker, post-traumatic transformations, changes in business life, and changes in the role of a service provider. Conclusions: As a result of the study, it was seen that the social relations, philosophy of life, belief systems, and self-perceptions of healthcare professionals were transformed after the disease-based trauma and innovations occurred in their lives. Also, positive and negative changes have been determined in the relationships of healthcare professionals who have experienced disease-based trauma with their colleagues and managers their sense of belonging to the organization, the way they provide health services, and their approach to patients. Highlights: There are advantages and disadvantages of being a health worker regarding disease-based traumas. Life transformations occur in social lives, psychology, and business conditions after trauma. These affect service delivery by enabling healthcare professionals to adopt the patient perspective. Policies should protect traumatized employees from further negative processes after trauma.